Assessment of microsurgery competency‐where are we now?. Issue 5 (24th May 2013) - Ramachandran, Savitha; Ghanem, Ali M.; Myers, Simon R.
<x xml:space="preserve">Abstract</x> In the last decade surgical training is being revolutionized by two novel concepts that have been introduced to almost all branches of surgery including and most recently to microsurgery. These two concepts are: objective assessments of surgical skills and the nurturing of surgical skills in a simulation laboratory setting. Acquiring surgical skills in the laboratory setting can help move the microsurgical learning curve from the patient to the laboratory and this will in turn improve patient safety. In order to optimize microsurgical training through a competency based training programme, it is imperative for microsurgical educators to understand microsurgical skill acquisition. This requires accurate objective assessment tools that can define and quantify microsurgical competency. This article aims to review the current literature on the various objective assessment tools adapted for microsurgery and attempt to identify the gaps that need to be addressed by research in microsurgical education to establish the ideal objective assessment tool. © 2013 Wiley Periodicals, Inc. Microsurgery 33:406–415, 2013.